Meaning, Context and Methodology - Conrad, Sarah-Jane; Petrus, Klaus (Mouton Series in Pragmatics [MSP], 2017)
What methodological impact does Contextualism have on the philosophy of language? This collection sets out to provide some answers. The authors in this volume question three ultimately connected assumptions of the philosophy of language. The first assumpt